Analisis Upaya Preventif dan Represif Penegakan Hukum Pidana terhadap Kekerasan Anak di Wilayah Hukum Kepolisian Sektor Kota Jambi - Oktir Nebi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study examines the enforcement of criminal law against child violence in the jurisdiction of the Jambi City Police Sector through a preventive and repressive approach. Children are the next generation of the nation who have the right to be protected from all forms of violence. Unfortunately, cases of violence against children still occur frequently, so effective law enforcement is needed to protect them. This study uses the theory of legal sociology to understand the relationship between law and social reality in the context of child protection. The research method used is qualitative, with data obtained through interviews and document analysis. Informants were selected using the Simple Random Sampling technique. The results of the study show that preventive efforts, such as socialization and education involving the Women's Empowerment and Child Protection Office (DP3A), have succeeded in increasing public awareness of child violence. On the other hand, repressive efforts are carried out strictly, where perpetrators of child violence who are proven guilty are subject to criminal sanctions in accordance with Law No. 35 of 2014 concerning Child Protection. However, challenges remain, especially related to the low reporting of cases of violence due to the culture of silence in the community. Stronger synergy between the government, the community, and law enforcement is needed to create a safer environment for children.